Marketing Strategy of Educational Services in Improving Competitiveness and Quality of Madrasah Aliyah in Menes Pandeglang - Fatoni, Ahmad; Bachtiar, Machdum; Fauzi, Anis (Attractive : Innovative Education Journal, 2024)
The number of educational institutions has implications for competitive competition in order to attract consumers to exist and have competitiveness. Menes is one of the heart of education in Pandeglang. To improve the competitiveness and quality of educational institutions, it is necessary to carry out marketing strategies so as to gain the trust of the community. This research aims: 1) To describe the marketing strategy of educational services of madrasah Aliyah in Menes Pandeglang; 2) Knowing the supporting and inhibiting factors of marketing strategy of educational services of madrasah Aliyah in Menes Pandeglang; 3) Describing the extent of marketing strategy of educational services as an effort to increase competitiveness and quality of madrasah Aliyah in Menes Pandeglang. The research method uses a descriptive qualitative approach with instruments of observation, interview, and documentation. The conclusions are: 1) The marketing strategy of educational services at MAS Mathla'ul Anwar, MAS Malnu Pusat, and MAS Anwarul Hidayah has implemented the concept of marketing mix, namely product, price, place, promotion, people, proof, and process; 2) Supporting factors for the marketing strategy of educational services of these three madrasas are strategic location, qualified human resources, affordable costs, and maximum service. The inhibiting factor is the limited funding of madrasah education; 3) Marketing strategy of education services greatly affects the competitiveness and quality of madrasah in Menes Pandeglang. So that these three madrasas continue to market educational services by improving the competence of human resources and infrastructure facilities.